2014
DOI: 10.3906/sag-1211-90
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A, fetuin-A, and pentraxin-3 levels in patients with ischemic stroke: novel prognostic biomarkers?

Abstract: A nonlinear process between co-propagating signal and control pulses has been proposed and demonstrated numerically, based on semiconductor optical amplifiers (SOA). Results show that a Gaussian signal pulse with picosecond duration can be simultaneously amplified and compressed in a SOA by utilizing a co-propagating high-intensity control pulse. To obtain high quality signal pulse with high peak power level and short pulse width, the center carrier wavelengths of two pulses should locate in the gain region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…SAA is also a sensitive marker of the acute inflammation and its serum concentrations increase in response to infection, trauma or stress. Whether SAA could be used as a specific diagnostic tool in AIS is still inconclusive [28,29]. Our study showed that the level of SAA was increased after stroke but did not show a significant relationship between SAA and serum sST2.…”
Section: Discussioncontrasting
confidence: 58%
“…SAA is also a sensitive marker of the acute inflammation and its serum concentrations increase in response to infection, trauma or stress. Whether SAA could be used as a specific diagnostic tool in AIS is still inconclusive [28,29]. Our study showed that the level of SAA was increased after stroke but did not show a significant relationship between SAA and serum sST2.…”
Section: Discussioncontrasting
confidence: 58%
“…Prior work has shown that PTX3 is an inflammatory marker associated with coronary artery disease (10). In cerebrovascular diseases, PTX3 represents baseline atherosclerotic burden more accurately in acute stroke and is related to the severity of the stroke (11). In order to reflect the level of PTX3 more timely and accurately, we detected the concentration of PTX3 within 48 h after ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Sezer et al (2014) investigated the levels of fetuin-A, Pentraxin-3, and serum amyloid A in a group of patients with ischemic stroke. Their results proved a signi cant correlation between the in ammatory factors and disease severity and progression [57]. The positive correlation between high plasma fetuin-A concentrations and a signi cantly higher risk of ischemic stroke and myocardial infarction was found in the patients from the EPIC-Potsdam Study with ischemic stroke and myocardial infarction [49,58].…”
Section: Fetuin a In Stroke Patientsmentioning
confidence: 89%